The role of self-existent owner in selected administrative proceedings and legal surveying processes - Pęska-Siwik, Agnieszka; Benduch, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
Ownership is the most important property law. It constitutes the foundation of rightly functioning society and sustainable economy. The role of owner in legal surveying processes and administrative proceedings related to real estate is specifi cally described in the law. The situation is more complicated in case of grounds with unsettled legal status. When it is impossible to determine the owner of real estate in the cadastre the data of people and organization units who rule these grounds based on principles of self-existent ownership are revealed. The self-existent owner rules the real estate as owner, but his role in an administrative proceedings like real estate delimitation as well as in legal surveying processes is not unambiguous. The goal of this article is the characterization of self-existent owner person and evaluation of his role during among others: determination of parcel boundaries, real estate delimitation, recovery of boundary marks or consolidation and exchange of lands. The rights and duties of self-existent owner are the main subject of the research. Possible legal solutions both: allowing effi cient and effective performing of analysed procedures and proceedings as well as ensuring respect for property rights are also indicated and discussed.